1982
DOI: 10.1002/ajp.1350030110
|View full text |Cite
|
Sign up to set email alerts
|

Blastogenic response of peripheral blood lymphocytes to mitogens in cynomolgus monkeys (Macaca fascicularis)

Abstract: Optimal conditions for mitogen-induced transformation of cynomolgus mon key peripheral blood lymphocytes were determined. Maximal stimulation estimated by the incorporation of tritiated thymidine ('H-TdR) occurred at the concentrations between 25 and 50 pglml with phytohemagglutinin (PHA) and concanavalin A (Con A), and between 50 and 100 pglml with poke weed mitogen (PWM) in a culture volume of 120 pl containing 2 x los mononuclear cells supplemented with 10% fresh autologous serum. Lipopolysaccharide (LPS), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

1982
1982
2003
2003

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 8 publications
(2 reference statements)
2
6
0
Order By: Relevance
“…Depression to Con A response was more than to PHA, and the degree of depression was more evident at higher lectin concentrations. This present result is similar to that of Tatsumi et al [1982], who showed adherent cells to be suppressive in cynomolgus monkey blastogenesis. These findings, however, are in contrast to published data for some mammalian species including humans, where adherent cells are essential for optimum mitogen-induced proliferation of lymphocytes [Geha & Merler, 1974;Rosenstreich et al, 1976;Habu & Raff, 1977;Mastro & Sniezek, 19841.…”
Section: Discussionsupporting
confidence: 92%
“…Depression to Con A response was more than to PHA, and the degree of depression was more evident at higher lectin concentrations. This present result is similar to that of Tatsumi et al [1982], who showed adherent cells to be suppressive in cynomolgus monkey blastogenesis. These findings, however, are in contrast to published data for some mammalian species including humans, where adherent cells are essential for optimum mitogen-induced proliferation of lymphocytes [Geha & Merler, 1974;Rosenstreich et al, 1976;Habu & Raff, 1977;Mastro & Sniezek, 19841.…”
Section: Discussionsupporting
confidence: 92%
“…The decline in IL 2 activity with culture time may be attributed to the adsorption of IL 2 by culture-generated lymphoblast oid cells possessing IL 2 receptors, as has been shown in other species [16,22], It was also shown in the cynomolgus monkey sys tem like in the murine system that Con A induced higher IL2 activity than PH A, while it was reported in human [ I ] and canine [5] systems that PHA induced higher 1L2 activity than Con A. These findings agreed with the previous observation that cynomol gus monkey lymphocytes showed higher blastogénie response to Con A than to PHA [28], Addition of PMA, known as a tumor promoter, re sulted in enhancement of IL2 production in lympho cyte cultures of cynomolgus monkeys, in agreement with the results obtained with murine cells [7], In con trast, the presence of xenogenic lymphoblastoid cell lines did not augment the 1L2 production whether they were of T or B cell origin; this is in contrast to the results obtained with human systems [3,14], The rea son for this discrepancy cannot be readily obtained. One possible explanation is that as promotion of IL 2 production by lymphoblastoid cell lines may be mod ulated by the presence of la antigens on the surface of cell lines [12,17], not enough cellular interaction to augment IL2 production through la antigens was conducted due to species difference between cyno molgus monkey lymphocytes and human cell lines.…”
Section: Discussionsupporting
confidence: 90%
“…Peripheral blood lymphocytes (PBL) were separated by gelatin sedimentation followed by a density gradient centrifugation, as previously described [28]. Spleens were asceptically removed from monkeys, teased apart and pressed through a stainless-steel mesh to produce a single-cell suspension in chilled RPMI 1640 medium.…”
Section: Preparation Of Leukocyte Suspensionsmentioning
confidence: 99%
“…demonstrated that, although the optimal culture conditions described earlier were systematically applied during subsequent lymphocyte proliferation assays, considerable variability was found from animal to animal. Previous studies have revealed the normal variability of the proliferative response in other primates (30, 32, 37, 41). We observed a persistent heterogeneity in the response amongst different individuals and particularly amongst different samples obtained from two separate bleedings (21 days interval) from the same donor.…”
Section: Discussionmentioning
confidence: 99%